1977
DOI: 10.1007/bf00011507
|View full text |Cite
|
Sign up to set email alerts
|

Development of salix and populus mycorrhizae in metallic mine tailings

Abstract: Roots of two year old willow and poplar planted as cuttings in copper and iron mine railings were stained intact and examined microscopically for mycorrhizal development. Incidence of mycorrhizae was related to tree vigor and to chemical and physical properties of the tailings. Results showed that no mycorrhizal development occurred on roots of these tree species in the copper railings; inoculations with natural forest soil extract failed to initiate this symbiosis. Tops and roots of the willow and poplar were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…At the intraspecific level, several authors have reported the existence of strains of both ectomycorrhizal, (Harris & Jurgensen, 1977) and vesiculararbuscular (VA) mycorrhizal fungi, (Lambert, Cole & Baker, 1980), which were specifically adapted to local edaphic conditions. Adaptation can be expressed in the present context as a differential ability of ectomycorrhizal associates of Betula to grow on agar containing raised zinc concentrations (Brown & Wilkins, 1985b), or of VA mycorrhizal strains to infect potential hosts in the presence of zinc (Gildon & Tinker, 1981, 1983.…”
Section: Introductionmentioning
confidence: 99%
“…At the intraspecific level, several authors have reported the existence of strains of both ectomycorrhizal, (Harris & Jurgensen, 1977) and vesiculararbuscular (VA) mycorrhizal fungi, (Lambert, Cole & Baker, 1980), which were specifically adapted to local edaphic conditions. Adaptation can be expressed in the present context as a differential ability of ectomycorrhizal associates of Betula to grow on agar containing raised zinc concentrations (Brown & Wilkins, 1985b), or of VA mycorrhizal strains to infect potential hosts in the presence of zinc (Gildon & Tinker, 1981, 1983.…”
Section: Introductionmentioning
confidence: 99%
“…from the U.K. (Brown & Wilkins, 1985). Under metal-contaminated field conditions, ectomycorrhizas may either fail to form, or the mycobiont involved may change (Gobi & Pumpel, 1973;Harris & Jurgensen, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…compared to noninoculated seedlings. Harris and Jurgensen (1977) found that cuttings of willow and hybrid poplar grew poorly on copper tailings in comparison to better growt.h on iron tailings. Better seedling growth and development on iron tailings in comparison to copper tailings was due to increased ectomycorrhizal development, better soil fertility and/or fewer toxic chemicals.…”
Section: Investigations Ofmentioning
confidence: 97%